Systematic review study on application of Ion Imprinted polymer (IIP) in heavy metals detection - Abdul Halim, Amanatuzzakiah; Sulaiman, Suhaili Syafiqah; Nordin, Anis Nurashikin; Hariz, Hikmah Bajunaid (Taylor & Francis, 2022)
Worldwide industrialisation and agriculture activities have led to a serious problem of environmental pollution due to the discharge of toxic contaminants in the watercourse and surroundings. When disposed in concentrations beyond the maximum limit, heavy metals can be a source of contamination to the environment. To monitor the level of contamination, electrochemical sensors can be utilised for qualitative and quantitative measures. They are known to be highly selective, less time consuming and lightweight. The portability of the sensors allows the measurement to be carried out onsite to ensure the environmental requirements are monitored. On the other hand, ion-imprinted polymers (IIPs) are developed to mimic the characteristics of the specific analyte for detection and overcome the limitations of natural biorecognition elements such as protein, enzyme and antibodies. Due to the growing interest in IIP application for heavy metals detection, a comprehensive review on the topic covering recent works, challenges and gaps in this area is required. In this mapping study, data from selected studies were extracted, organised, and categorised by implementing a systematic mapping process. From 340 studies, a total of 51 studies were included after the two-step screening phase, and data obtained were extracted and mapped under four classification schemes. One research question and two sub-questions were addressed with the data extracted from all included studies. The sub-questions derived from the main research question are on the surface modifications of the working electrode of the sensors and their area of applications. The research gaps were identified and addressed with several recommendations for further development in the area related to the application of ionimprinted polymers for heavy metals detection.